PENGARUH GAYA KEPEMIMPINAN DAN PELATIHAN KERJATERHADAP KINERJA KARYAWAN PADA PT GEMA RORINDO ANUGERAH - Ivan Dean Satriani; Bambang Sutarto (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The purpose of this study was to determine the effect of leadership style and work training both partially and simultaneously on employee performance at PT Gema Rorindo Anugerah with a sample of 50 employees. The method used is a quantitative method. Data analysis used in this study is data instrument testing, classical assumption testing, linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and F test. The coefficient of determination X2 is 46.8% while the remaining 53.2% is caused by other variables not examined in this study. Leadership Style and Job Training simultaneously have a significant effect on Employee Performance with the regression equation Y = 10.737 + 0.258 X1 + 0.499 X2. The results of testing the first hypothesis obtained a value of t count> t table or (5.127> 1.678). Based on the results of testing the second hypothesis, the value of t count> t table or (6.493> 1.678) was obtained. Based on the results of the third hypothesis test, the F count value was obtained 23.273 > F table 3.195. This shows that simultaneously the variables of leadership style and work training have a significant influence on employee performance.